Unilateral Lichen Planus: A Rare Case Report - Jha, Niharika; Kanish, Bimal; Bhatia, Anuradha (Nepal Journal of Dermatology, Venereology & Leprology, 2018)
Lichen planus (LP) is a papulosquamous disorder characterized by violaceous, flat topped papules and plaques seen on the volar aspect of the wrists, lumbar region and around the ankles. It can have a varied presentation. Here we describe a rare variant of LP in a female who presented with unilateral eruptions of violaceous papules over the right side of the body.